Laju Sedimentasi di Dataran Banjir Sungai Ciujung Hulu Berdasarkan Profil Pb-210 Excess - Aliyanta, Barokah; Suhartini, Nita (EKSPLORIUM, 2018)
The rate of deposition of sediment on the floodplain area is one of the constituent component of the sediment budget in watersheds. Therefore, the sedimentation rate estimation has been made in two locations of the floodplains based on the age sediment obtained using Pb-210 excess technique. Sediment cores were taken in the Ciujung Hulu River floodplain every 10 cm depth intervals up to a depth of 120 cm. Sediment was obtained then dried, disaggregated, sifted, weighing 150–300 gr, placed into the special containers and tightly closed. After a month in a sealed condition, samples were measured using gamma spectrometer Multichannel analyzer (MCA) to find out the activity of Pb-210 total and Pb-210 supported. Based on the data of Pb-210 total and Pb-210 supported, there are three different ways to get Pb-210 excess profiles. Obtained Pb-210 excess data is used to calculate the age of the sediments on the basis of the method of constant rate of supply (CRS). Through the age of sediment layers, can be recognized the existence of transitional zone of sediment deposition rate at both locations. The rate of sedimentation ranged from 1.028 cm/year from the years 1968–1987, and rose to about 2.83 cm/year from the years 1987–2016 (28.95 years) at location 1. While in location 2, the rate of sedimentation ranged 0.676 cm/year from the years 1950–1993, and rose to about 3.231 cm/year from the years 1993–2016 (2 years).